Complex prospective memory in adults with attention deficit hyperactivity disorder - Fuermaier, Anselm B. M.; Tucha, Lara; Koerts, Janneke; Aschenbrenner, Steffen; Westermann, Celina; Weisbrod, Matthias; Lange, Klaus W.; Tucha, Oliver (PLOS ONE, 2013)
Objectives Attention deficit hyperactivity disorder (ADHD) in adults has been associated with disturbances of attention and executive functions. Furthermore, impairments of verbal and figural retrospective memory were reported. However, little is known about the effects of ADHD on prospective memory, the execution of delayed intentions in the future. Methods The present study compared the performance of 45 adult patients with ADHD not treated with stimulant medication with the performance of 45 matched healthy individuals on a paradigm of complex prospective memory which measured task planning, plan recall, self-initiation and execution. Furthermore, the contribution of other cognitive functions to prospective memory functioning was assessed, including measures of attention, executive functions and memory. Results A large-scale impairment could be observed in task planning abilities in patients with ADHD. Only negligible to small effects were found for plan recall, self-initiation and execution. Inhibition was identified to contribute significantly to performance on task planning. Conclusions The present findings suggest that four cognitive components contribute to the performance of prospective memory. Impairments of prospective memory mainly emerged from deficient planning abilities in adults with ADHD. Implications on behavioral based intervention strategies are discussed.